2011
DOI: 10.1016/j.resp.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of synaptic transmission to respiratory motoneurons

Abstract: Respiratory motoneurons provide the exclusive drive to respiratory muscles and therefore are a key relay between brainstem neural circuits that generate respiratory rhythm and respiratory muscles that control moment of gases into and out of the airways and lungs. This review is focused on postnatal development of fast ionotropic synaptic transmission to respiratory motoneurons, with a focus on hypoglossal motoneurons (HMs). Glutamatergic synaptic transmission to HMs involves activation of both non-NMDA and NMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…In addition, Sebe et al (2006) reported that GABAergic and glycinergic transmission are required to generate robust synchronous burst oscillations of neurons in 12 N over postnatal development. This result and our data suggest that decreasing of [Cl À ] i during development might increase the frequency of burst oscillations of neurons in 12 N. Since this phenomenon cause that the time course of inhibitory synaptic transmission speeds up with postnatal development (Berger, 2011), it means that the duration time of RRA could be decreased. Therefore, neurons in 12 N might prepare for the next burst activity very quickly but it is still unclear that inhibitory GABAergic responses can increase the RRA frequency.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, Sebe et al (2006) reported that GABAergic and glycinergic transmission are required to generate robust synchronous burst oscillations of neurons in 12 N over postnatal development. This result and our data suggest that decreasing of [Cl À ] i during development might increase the frequency of burst oscillations of neurons in 12 N. Since this phenomenon cause that the time course of inhibitory synaptic transmission speeds up with postnatal development (Berger, 2011), it means that the duration time of RRA could be decreased. Therefore, neurons in 12 N might prepare for the next burst activity very quickly but it is still unclear that inhibitory GABAergic responses can increase the RRA frequency.…”
Section: Discussionsupporting
confidence: 67%
“…A consideration of the major gaps in our understanding of tongue muscle and hypoglossal motoneuron anatomy and physiology is considered next (Fregosi, 2011), followed by a detailed discussion of the respiration-related and volitional control of genioglossus muscle motor units (Bailey, 2011). The issue concludes with a consideration of how synaptic transmission in the hypoglossal motoneuron pool develops (Berger, 2011), as well as how excitotoxic and oxidative stress alters the function of developing hypoglossal motoneurons (Cifra et al, 2011). …”
Section: Forewordmentioning
confidence: 99%
“…The main source of GABAergic and glycinergic inhibitory inputs to the HNs derives from the nucleus of Roller (2, 62), which affect the HNs via activation of postsynaptic GABA A and glycine receptors (2, 5, 52, 62). These inhibitory synaptic inputs control hypoglossal responses to other synaptic inputs, shape the temporospatial pattern of neuronal activity during reflex and rhythmic behaviors, and contribute to the generation of inspiratory motoneuronal synchrony (5,49,53).The strength of these synaptic inhibitions of HNs is modulated by brainstem norepinephrine (NE) systems by ␣-adrenoceptors (18). The ␣-adrenoceptors contain two main types including ␣ 1 and ␣ 2 , each comprising at least three subtypes (13, 42).…”
mentioning
confidence: 99%
“…The HNs receive excitatory and inhibitory synaptic inputs (1,7,19,47,51,69). The main source of GABAergic and glycinergic inhibitory inputs to the HNs derives from the nucleus of Roller (2,62), which affect the HNs via activation of postsynaptic GABA A and glycine receptors (2,5,52,62). These inhibitory synaptic inputs control hypoglossal responses to other synaptic inputs, shape the temporospatial pattern of neuronal activity during reflex and rhythmic behaviors, and contribute to the generation of inspiratory motoneuronal synchrony (5,49,53).…”
mentioning
confidence: 99%
See 1 more Smart Citation